RUN1 and REN1 Pyramiding in Grapevine (Vitis vinifera cv. Crimson Seedless) Displays an Improved Defense Response Leading to Enhanced Resistance to Powdery Mildew (Erysiphe necator) - Agurto, Mario; Schlechter, Rudolf O.; Armijo, Grace; Solano, Esteban; Serrano, Carolina; Contreras, Rodrigo A.; Zúñiga, Gustavo E.; Arce-Johnson, Patricio (Frontiers in Plant Science, 2017)
Fungal pathogens are the cause of the most common diseases in grapevine and among them powdery mildew represents a major focus for disease management. Different strategies for introgression of resistance in grapevine are currently undertaken in breeding programs. For example, introgression of several resistance genes (R) from different sources for making it more durable and also strengthening the plant defense response. Taking this into account, we cross-pollinated P09-105/34, a grapevine plant carrying both RUN1 and REN1 pyramided loci of resistance to Erysiphe necator inherited from a pseudo-backcrossing scheme with Muscadinia rotundifolia and Vitis vinifera ‘Dzhandzhal Kara,’ respectively, with the susceptible commercial table grape cv. ‘Crimson Seedless.’ We developed RUN1REN1 resistant genotypes through conventional breeding and identified them by marker assisted selection. The characterization of defense response showed a highly effective defense mechanism against powdery mildew in these plants. Our results reveal that RUN1REN1 grapevine plants display a robust defense response against E. necator, leading to unsuccessful fungal establishment with low penetration rate and poor hypha development. This resistance mechanism includes reactive oxygen species production, callose accumulation, programmed cell death induction and mainly VvSTS36 and VvPEN1 gene activation. RUN1REN1 plants have a great potential as new table grape cultivars with durable complete resistance to E. necator, and are valuable germplasm to be included in grape breeding programs to continue pyramiding with other sources of resistance to grapevine diseases.